Opioid Use in the United States - Berger, Paul D (Advances in Social Sciences Research Journal, 2019)
Our paper focuses on studying drivers of individual drug user relapse as well as broader systematic drug use patterns across states in the United States of America. For this study, two datasets were used; the first is a subset of the survey results from Dr. Miriam Boeri’s co-authored study, “Older Drug Users: A Life Course Study of Turning Points in Drug Use [in a large Southeastern Metropolitan Area], 2009-2010”. The dataset included variables such as the gender, race, education level, the age at which the respondents moved away from their guardian’s home, and the age at which the respondent filled the survey. With this dataset, a logistic regression analysis is preformed to identify factors that may be associated with drug relapse. We found that the only “somewhat important” factor, as compared to all the factors studied, seemed to be “the current age of the respondent when they interviewed.” The second dataset is composed of variables such as the state-wise population density, GDP, median household income, opioid prescription rate, death rate due to overuse of opioids, alcohol consumption rate, death rate due to alcohol overuse, death rate due to drug overuse, suicide death rate, and education attainment level across the United States.